Głosowanie elektroniczne jako alternatywna metoda uczestniczenia w wyborach – opinie Polaków - Musiał-Karg, Magdalena (Political Preferences, 2015)
Electronic voting as an alternative method of participation in the elections – opinions of Poles The research subject of this paper are the opinions of Poles on the implementation of one of the alternative methods of voting in elections and referendums - an electronically assisted voting. The main aim of the author is the analysis of the attitudes of Poles on the idea of establishment of e-voting in Poland, and their declarations regarding the use of e-voting (if such possibility). The findings would be supplemented with selected data from the public opinion polls realized by the Office of Human Rights Defender (Ombudsman). Key words: electronic voting, e-voting, Internet voting, opinions of Poles